The Effect Of Meditation On Improving The Academic Achievement Of Grade XI Students - Acep, Lauw; Putra, Pratama Eka (CV Putra Publisher, 2026)
This study evaluates the effect of meditation on the academic performance of Grade XI students at SMAN 1 Tanjung Lombok Utara who were experiencing concentration decline due to academic stress. Using a quantitative quasi-experimental design, two classes were purposively selected: an experimental class (n = 32) received a 10-minute daily meditation session before lessons for six weeks, while a control class (n = 32) followed regular instruction. Academic performance was measured by mid-term exam scores, whereas concentration and stress were assessed with a concentration scale and the DASS-21 before and after the intervention. Mixed-ANOVA revealed that the mean score gain in the experimental class (Δ = 8.7 points) was significantly higher than in the control class (Δ = 2.1 points), F(1,62) = 42.3, p < 0.001, η² = 0.41. Stress scores dropped by 23 % and concentration index rose by 18 % in the experimental class; no significant changes occurred in the control class. It is concluded that brief school-based meditation effectively improves academic achievement, reduces stress, and enhances students’ focus. The intervention can serve as a low-cost strategy to support mental-academic balance in senior high schools